2010
DOI: 10.1007/s11663-010-9436-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Modeling of Supersonic Coherent Jets for Electric Arc Furnace Steelmaking Process

Abstract: Supersonic coherent gas jets are now used widely in electric arc furnace steelmaking and many other industrial applications to increase the gas-liquid mixing, reaction rates, and energy efficiency of the process. However, there has been limited research on the basic physics of supersonic coherent jets. In the present study, computational fluid dynamics (CFD) simulation of the supersonic jet with and without a shrouding flame at room ambient temperature was carried out and validated against experimental data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 18 publications
0
53
0
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Tago and Higuchi 4 investigated single and multiple nozzle jet behaviour based on fluid dynamics, and the results showed that the numerical simulations were consistent with experimental results. Odenthal et al 8,9 simulated single nozzle supersonic jet behaviour by CFD modelling based on a steady and compressible mathematical model.…”
Section: Introductionmentioning
confidence: 91%
“…[4][5][6][7][8][9][10][11][12] Tago and Higuchi 4 investigated single and multiple nozzle jet behaviour based on fluid dynamics, and the results showed that the numerical simulations were consistent with experimental results. Odenthal et al 8,9 simulated single nozzle supersonic jet behaviour by CFD modelling based on a steady and compressible mathematical model.…”
Section: Introductionmentioning
confidence: 91%
“…Nowadays, the availability of very accurate computational fluid-dynamics is a very powerful modeling tool to support engineers in the conception and selection of the best design solutions [2,3,4]. MORE nozzle for oxygen injection was generated thanks to this advanced approach.…”
Section: The Process Optimization Of the Oxygen Lancingmentioning
confidence: 99%
“…O resíduo especificado foi de 10 No modelo de turbulência κ-ε padrão, a viscosidade turbulenta é calculada pela equação 8, onde Cµ é 0.09, constante. No presente trabalho, o modelo de turbulência utilizado foi o modelo κ-ε adaptado para jatos supersônicos em ambientes quentes, sugerido por Alam et al [10] onde, o Cµ é modificado conforme as equações 9, 10, 11 e 12. Assim os efeitos da compressibilidade e temperatura, que afetam o número de Mach, são considerados.…”
Section: Materiais E Métodosunclassified